Daily Gene Expression Rhythms in Rat White Adipose Tissue Do Not Differ Between Subcutaneous and Intra-Abdominal Depots - van der Spek, Rianne; Fliers, Eric; la Fleur, Susanne E.; Kalsbeek, Andries (Frontiers in Endocrinology, 2018)
White adipose tissue (WAT) is present in different depots throughout the body. Although all depots are exposed to systemic humoral signals, they are not functionally identical. Studies in clock gene knock-out animals and in shift workers suggest that daily rhythmicity may play an important role in lipid metabolism. Differences in rhythmicity between fat depots might explain differences in depot function; therefore we measured mRNA expression of clock genes and metabolic genes on a 3-hour interval over a 24-hour period in the subcutaneous inguinal depot and in the intra-abdominal perirenal, epididymal and mesenteric depots of male Wistar rats. We analysed rhythmicity using CircWave software. Additionally, we measured plasma concentrations of glucose, insulin, corticosterone and leptin. The clock genes (Bmal1/Per2/Cry1/Cry2/RevErbα/DBP) showed robust daily gene expression rhythms, which did not vary between WAT depots. Metabolic gene expression rhythms (SREBP1c/PPARα/PPARγ/FAS/LPL/Glut4/HSL/CPT1b/leptin/visfatin/resistin) were more variable between depots. However, no distinct differences between intra-abdominal and subcutaneous rhythms were found. Concluding, specific fat depots are not associated with differences in clock gene expression rhythms and therefore do not provide a likely explanation for the differences in metabolic function between different fat depots.